Effect of Cr content in temperature-dependent mechanical properties and strain hardening of a twinning-induced plasticity steel - De Barbieri, Flavio; Jorge Badiola, Denis; Allende, Rodrigo; Tello, Karem; Artigas, Alfredo; Perazzo, Franco; Jami, Henry; Perez Ipiña, Juan Elias (Elsevier Science SA, 2024)
Fil: De Barbieri, Flavio. Universidad Técnica Federico Santa María; Chile